Unternehmer und Grundherren Nord-Nigerias im Kampf um die politische Macht: Zum sozialen Aufstieg der einheimischen Wirtschaftselite in den nigerianischen Emiraten - Dirk Kohnert (Africa Spectrum, 1978)
The traditional relationship of patronage and clientship between the landlords and the growing commercial class in Bida and in other Nigerian Emirates - firmly established during the 19th century - left indelible marks which influenced the pattern of social communication between these two classes till today. Up to the fifties of the 20th century there existed a strong interdependence between the landed aristocrats — dominant in government and Native Administration — and the rich merchant-traders who took up the burden to act as “ bankers" of the traditional leisured class in order to promote their own social status. The indigenous entrepreneurs gradually became more independent as the traditional rulers had to offer popular businessmen participation in political organisations to counteract the increasing resistance of the talakawa (the commoners) against the emirate system during the era of formal democratization (1954-1966). The national bourgeoisie of the North seized this opportunity to call for a higher degree of protection both against the more successful merchant-capital of the South and the powerful foreign companies which at that time dominated nearly all of the profitable sectors of investment either in trade or in industry. Far from being a fetter to the growth of a new class of Nigerian entrepreneurs, the traditionally minded landlords - side by side with the indigenous merchant-traders - secured a remarkably high degree of economic growth and independence during the past two decades in Northern Nigeria, compared with other parts of Nigeria. – – Les entrepreneurs et les seigneurs de terre du Nigeria du nord dans leurs lutte pour le pouvoir politique: Sur l'ascension de l'élite économique autochtone dans les émirats nigérians La relation traditionnelle de patronage et de clientélisme entre les seigneurs de terre et la classe commerciale croissante à Bida et dans l'autres émirats nigérians - fermement établi au cours du 19e siècle - laissé des traces indélébiles qui influent sur le modèle de la communication sociale entre ces deux classes, même aujourd'hui. Jusqu'aux années cinquante du 20ième siècle, il existait une forte interdépendance entre les seigneurs de terre - dominante au sein du gouvernement et de l'administration locale - et les riches marchands-commerçants qui ont pris la charge d'agir comme «banquiers» de la classe dirigeante traditionnelle afin de promouvoir leur propre statut social. Les entrepreneurs autochtones sont progressivement devenus plus indépendants. C'était la raison pour laquelle les chefs traditionnels aient à offrir les hommes d'affaires populaires une plus grande participation dans l'organisation politique pour contrer la résistance croissante des talakawa (da la paysannerie) contre le système de l'émirat pendant l'ère de la démocratie formelle (1954 -1966). La bourgeoisie nationale du Nord a saisi cette occasion pour appeler à un degré plus élevé de protection à la fois contre le capital commerçant du Nigeria du Sud plus performant et des puissantes compagnies étrangères du Sud et qui à l'époque ont dominé presque tous les secteurs rentables de l'investissement soit dans le commerce ou dans l'industrie. Loin d'être une entrave à la croissance d'une nouvelle classe d'entrepreneurs nigérians, les seigneurs de terre traditionnels, côte à côte avec les marchands commerçants autochtones – ont atteints un degré élevé remarquable de la croissance économique et de l'indépendance au cours de la deux dernières décennies dans le Nigeria du Nord, par rapport à d'autres régions du Nigeria.
Additional information: Author's version
Keywords: Z13; P16; O12; N47; P48; O17; 330; class formation; rural development; Nigeria; Afrika; African contemporary history; Klassenkampf; Soziale Schicht; Nigeria; Subsahara-Afrika